ANALISIS KINERJA DAN LINGKUNGAN INTERNAL EKSTERNAL AGROINDUSTRI KERIPIK PISANG (STUDI KASUS DI DESA SUNGAI LANGKA KABUPATEN PESAWARAN) - Rizky Marliani Putri; Dwi Haryono; Adia Nugraha (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2019)
This research aims to analyze the management of raw materials procurement, management of supply chain, production performance, and also to analyze the internal and the external environmental conditions of banana chips agroindustries. This research was conducted in Sungai Langka Village of Pesawaran Regency. This location was selected purposively with consideration that Sungai Langka Village was the only village in Pesawaran Regency which was built by University of Lampung  as Village Laboratory that actively produce banana chips. The total respondents were 6 people consisting of one owner and one worker from each industry. Data were collected in December 2017 until January 2018. This research is using descriptive qualitative and descriptive quantitative methods. The results showed that banana chips agroindustries did not procure raw materials on time and exact amount.  However, management of supply chain and performance of banana chips agroindustries in Sungai Langka Village have been going well. The average productivity was 11.10 kg/working day and the average capacity was 78 percent.Key words: agroindustry, banana chips, environmental, and performance